2022
DOI: 10.1155/2022/5676570
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Validation of a Machine Learning Prediction Model Based on Big Data for Predicting the Risk of Bone Metastasis in Renal Cell Carcinoma Patients

Abstract: Purpose. Since the prognosis of renal cell carcinoma (RCC) patients with bone metastasis (BM) is poor, this study is aimed at using big data to build a machine learning (ML) model to predict the risk of BM in RCC patients. Methods. A retrospective study was conducted on 40,355 RCC patients in the SEER database from 2010 to 2017. LASSO regression and multivariate logistic regression analysis was performed to determine independent risk factors of RCC-BM. Six ML algorithm models, including LR, GBM, XGB, RF, DT, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Xu et al used the ML method to predict bone metastasis in renal cell carcinoma. The comparison of evaluation indexes among various ML methods showed that the XGB ML model had the highest AUC (0.891) in clinical prediction 33 . In addition, Jiang et al used the XGB model combined with deep learning for early identification of preoperative microvascular invasion in HCC patients, and the differential rate of the AUC could reach 0.906 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al used the ML method to predict bone metastasis in renal cell carcinoma. The comparison of evaluation indexes among various ML methods showed that the XGB ML model had the highest AUC (0.891) in clinical prediction 33 . In addition, Jiang et al used the XGB model combined with deep learning for early identification of preoperative microvascular invasion in HCC patients, and the differential rate of the AUC could reach 0.906 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of evaluation indexes among various ML methods showed that the XGB ML model had the highest AUC (0.891) in clinical prediction. 33 In addition, Jiang et al used the XGB model combined with deep learning for early identification of preoperative microvascular invasion in HCC patients, and the differential rate of the AUC could reach 0.906. 34 In our study, because the probability of OM in PLC patients is low, even when the data of PLC patients were collected for 14 years, the incidence of OM was only 1.3%.…”
Section: Modelmentioning
confidence: 99%
“…[81] Bone metastases occur in about 20% to 35% of patients with mRCC, and these patients have a 5-year survival rate of <11%. [82] Predominantly osteolytic, these bone metastases lead to extensive skeletal destruction. Consequently, many patients with RCC experience skeletal-related events (SREs), such as pain, fractures, and nerve compression, particularly in advanced disease stage.…”
Section: The Site Of Rcc Metastasismentioning
confidence: 99%
“…Due to the huge data in the SEER database and the scientific nature of the new algorithm, the model performance has been improved. However, the rationality and completeness of the included variables still need to be improved, and the performance evaluation also needs to be supplemented ( 18 ).…”
Section: Introductionmentioning
confidence: 99%